Influence of weekday of admission and level of distress on length of hospital stay in patients with low back pain: a retrospective cohort study - Brunner, Emanuel; Meichtry, André; Vancampfort, Davy; Imoberdorf, Reinhard; Gisi, David; Dankaerts, Wim; Graf, Anita; Wipf Rebsamen, Stefanie; Suter, Daniela; Wildi, Lukas Martin; Buechi, Stefan; Sieber, Cornel (BMC Musculoskeletal Disorders, 2021)
Background: Low back pain (LBP) is often a complex problem requiring interdisciplinary management to address patients’ multidimensional needs. Providing inpatient care for patients with LBP in primary care hospitals is a challenge. In this setting, interdisciplinary LBP management is often unavailable during weekends. Delays in therapeutic procedures may result in a prolonged length of hospital stay (LoS). The impact of delays on LoS might be strongest in patients reporting high levels of psychological distress. Therefore, this study investigates the influence of weekday of admission and distress on LoS of inpatients with LBP. Methods: This retrospective cohort study was conducted between 1 February 2019 and 31 January 2020. In part 1, a negative binomial model was fitted to LoS with weekday of admission as a predictor. In part 2, the same model included weekday of admission, distress level, and their interaction as covariates. Planned contrast was used in part 1 to estimate the difference in log-expected LoS between group 1 (admissions Friday/Saturday) and the reference group (admissions Sunday-Thursday). In part 2, the same contrast was used to estimate the corresponding difference in (per-unit) distress trends. Results: We identified 173 patients with LBP. The mean LoS was 7.8 days (SD = 5.59). Patients admitted on Friday (mean LoS = 10.3) and Saturday (LoS = 10.6) had longer stays, but not those admitted on Sunday (LoS = 7.1). Analysis of the weekday effect and planned contrast showed that admission on Friday or Saturday was associated with a significant increase in LoS (log ratio = 0.42, 95% CI = 0.21 to 0.63). A total of 101 patients (58%) returned questionnaires, and complete data on distress were available from 86 patients (49%). According to the negative binomial model for LoS and the planned contrast, the distress effect on LoS was significantly influenced (difference in slopes = 0.816, 95% CI = 0.03 to 1.60) by dichotomic weekdays of admission (Friday/Saturday vs. Sunday-Thursday). Conclusions: Delays in interdisciplinary LBP management over the weekend may prolong LoS. This may particularly affect patients reporting high levels of distress. Our study provides a platform to further explore whether interdisciplinary LBP management addressing patients’ multidimensional needs reduces LoS in primary care hospitals.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Low back pain; Mental health; Pain management; Primary care; Primary care hospital